Новый синоним Merodon tricinctus (Diptera, Syrphidae) - Попов, Г.В. (Вестник зоологии, 2000)
Merodon karadaghensis Zimina, 1989 явля ется младшим субъективним синонимом Merodon tricinctus Sack, 1913. Показана внутривидовая изменчивость во внешней морфологии имаго и в строении гипопигия. Наиболее изменчива форма сурстилей; у экземпляров из Югославии отсутствует налет на лице. Кратко охарактеризован ареал (с указанием новых мест находок), биотопическое распределение и численность вида. Merodon karadaghensis Zimina, 1989 is shown to be a junior subjective synonym of Merodon tricinctus Sack, 1913. External morphology of adults and structure of hypopygium is shown to be variable. The most variable is the shape of surstyli, and the tomentum of face is absent in specimens from Yugoslavia. Distribution range, new records, biotopical distribution and size range of the species are briefly characterized.